AMPLIFY-7P: Phase 1 and randomized phase 2 study of amphiphile immunotherapy ELI-002 7P as adjuvant treatment for subjects with G12D, G12R, G12V, G12C, G12A, G12S and G13D Kirsten rat sarcoma (KRAS)-mutated pancreatic ductal adenocarcinoma - Chung, Vincent; Devoe, Craig E.; George, Thomas J.; Welkowsky, Esther; Kheoh, Thian; Haqq, Christopher M.; Pant, Shubham; O'Reilly, Eileen Mary (Journal of clinical oncology, 2024)
TPS720Background: KRAS mutations occur in 25% of human tumors, frequently in pancreatic where over 85% relapse after locoregional treatment. ELI-002 7P is a lymph node targeted immunotherapy comprised of Amphiphile (Amph)-modified G12D, G12R, G12V, G12C, G12A, G12S and G13D mutant KRAS peptides together with an Amph-modified CpG oligonucleotide adjuvant. In the first in human AMPLIFY-201 study, a two peptide G12D/G12R formulation increased KRAS-specific T cells in 87% of patients, and T cell responses 13-fold or higher over baseline correlated with outcomes including reduction in risk of relapse or death. The AMPLIFY-7P study hypothesizes that adjuvant administration of ELI-002 7P will be safe and will delay relapse compared to observation in patients with KRAS mutated pancreatic cancers who have completed curative intent locoregional treatment. Methods: This open-label, phase 1 and randomized phase 2 study is evaluating ELI-002 7P in patients with KRAS mutated pancreatic adenocarcinoma following standard of care chemotherapy and surgery. In phase 2, patients are randomized 2:1 to ELI-002 7P versus observation with crossover of the observation arm permitted at the time of confirmed radiographic relapse via iRECIST. Eligible patients must be within 6 months of completion of locoregional treatment for up-front resectable pathologically confirmed pancreatic cancer (Stage I-III) with radiographic NED (no evidence of disease). Phase 2 patients are included regardless of biomarker evidence of recurrent disease, however, those who have not recovered absolute lymphocytes to the normal range following cytotoxic therapy are excluded. The primary phase 2 objective is to compare the efficacy of ELI-002 7P versus observation, with primary endpoint disease-free survival per investigator. Secondary objectives compare biomarker response (reduction or clearance of ctDNA or if ctDNA was not detectable, serum tumor antigen CA19-9) in the subset with positive baseline values, OS, safety, and iRECIST response rate in the crossover subset. Exploratory endpoints include immunogenicity, the association of immunogenicity with high resolution HLA typing, and evaluation of tumor-infiltrating T cells and the tumor microenvironment in the event biopsy tissue is available. An Independent Data Monitoring Committee reviewed phase 1 data and recommended opening phase 2. Subsequent patients will receive up to 10 doses of Amph-peptides 7P 700 mcg each (4.9 mg total), together with Amph-CpG-7909 (10.0 mg) administered over a five-month treatment period. In Phase 2, approximately 135 patients will be enrolled in the United States. An interim analysis is planned using group sequential design for control of overall alpha 0.10. Clinical trial information: NCT05726864.